2013
DOI: 10.1163/22941932-00000030
|View full text |Cite
|
Sign up to set email alerts
|

Axial conduit widening in woody species: a still neglected anatomical pattern

Abstract: Within a tree the lumen of the xylem conduits varies widely (by at least 1 order of magnitude). Transversally in the stem conduits are smaller close to the pith and larger in the outermost rings. Axially (i.e. from petioles to roots) conduits widen from the stem apex downwards in the same tree ring. This axial variation is proposed as being the most efficient anatomical adjustment for stabilizing hydraulic path-length resistance with the progressive growth in height. The hydrodynamic (i.e. physical) constraint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
141
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(156 citation statements)
references
References 6 publications
14
141
0
1
Order By: Relevance
“…Vessel diameter is a crucial parameter in the identification of plant adaptation strategy to survive in specific environmental conditions (Sperry et al 2006). Available literature indicates that the variation in vessel diameter is associated with habitat of the tree species and at various height of a tree (Anfodillo et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Vessel diameter is a crucial parameter in the identification of plant adaptation strategy to survive in specific environmental conditions (Sperry et al 2006). Available literature indicates that the variation in vessel diameter is associated with habitat of the tree species and at various height of a tree (Anfodillo et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In Q. alba, also belonging to the white oaks subgroup as Q. faginea, Phelps & Workman (1994) found that site quality was only expressed in the vessel proportion of trees at younger ages. According to Anfodillo et al (2013), tree size largely contributes to determine the vessel diameter, meaning that for the same age trees at site 1 seem to be taller showing wider vessels than trees grown at site 2. The decrease of ring width with age corresponded to a more constant vessel area and number, and to an increase of vessel frequency and proportion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the number of studies focusing on the variation of vessel features (e.g., with age, growth and site) and their relation to other wood characteristics (e.g., density) has increased, although data is still scanty and results are often species-specific. The main tendencies in studies on vessel diameter variation have been recently discussed by Anfodillo et al (2013), with special attention to the relationship between axial conduit widening and tree height.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current researches also indicate that observed differences, when considering the diameter of xylem vessel among different environments, are primarily driven by plant length (diameter's and trunk's height). Those are strictly related to the weather conditions and indirectly lead to a relation between vessel sizes and climate (ANFODILLO et al 2013;OLSON;ROSELL, 2013;LONGUI et al 2014).…”
Section: Introductionmentioning
confidence: 99%